Use of food additives in bakery products - Karim Sattarov; Abror Jankurazov; Javsurbek Khazratkulov (Наукові горизонти)
The influence of various food additives including emulsifiers (mono- and diglycerides of fatty acids (E471), lecithin (E322), sodium stearoyl-2-lactylate (E481) and preservatives (potassium sorbate (E202), sodium propionate (E281)) on the quality and shelf life of bakery products was investigated. The study was conducted on the basis of the enterprise in Gulistan (Uzbekistan) in order to improve organoleptic characteristics of products and extend their shelf life. To conduct the experiment, test batches of bread with the addition of the specified food additives in various combinations were made. The effect of additives on such parameters as softness and elasticity of crumb, porosity, moisture, as well as resistance to microbiological spoilage (yeast and mould) was analysed. Microbiological analysis showed that the addition of preservatives significantly reduced the number of colony-forming units (CFU) of yeasts and moulds in bakery products. The control group reached 500 CFU/g by day 7, while the combination group had the lowest levels of only 50 CFU/g on day 7, which confirmed the effectiveness of the preservatives. It was also observed that the use of the combination of emulsifiers E471 and E481 resulted in a significant improvement in bread texture, increased bread volume and improved crumb porosity. The addition of lecithin (E322) contributed to moisture retention, which slowed down the staling process. The addition of potassium sorbate and sodium propionate significantly increased the shelf life of the bakery products, preventing the development of mould and yeast during 7-10 days of storage in a climate-controlled chamber. Thus, the use of combinations of food additives in conditions of industrial production allowed improving the physical and chemical properties of bakery products, increased their shelf life and ensured microbiological safety of products. The results of the study may be useful for further implementation of these technologies in the bakery industry of the Republic of Uzbekistan